2022
DOI: 10.21203/rs.3.rs-1482666/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pregnancy Outcomes and Associated Factors in Women with Cardiovascular Diseases

Abstract: Background: Worldwide, cardiovascular diseases are among the leading cause of death, representing about a third of all global deaths. Of these deaths, 85% were due to heart attack and stroke. While existing evidences reveal that pregnancy in women with cardiovascular disease is associated with a range of feto-maternal complications, corresponding studies among pregnant women in Ethiopian context are rather limited. Thus, the aim of this study was to assess pregnancy outcomes and associated factors in women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Out of 100 patients, maternal mortality in our study was 6% which was comparable with other studies (2.7-8.1%). 7,12,15 A study published in European Cardiology Review (ECR) by Poli et al reported maternal death to be slightly higher at 12%. 16 Causes of death were acute pulmonary edema and congestive cardiac failure.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 100 patients, maternal mortality in our study was 6% which was comparable with other studies (2.7-8.1%). 7,12,15 A study published in European Cardiology Review (ECR) by Poli et al reported maternal death to be slightly higher at 12%. 16 Causes of death were acute pulmonary edema and congestive cardiac failure.…”
Section: Discussionmentioning
confidence: 99%